Overview of the causes of the October Revolution through the supplemented analysis of Theda Skocpol - Vojnović, Sava (Sociološki pregled, 2023)
Starting from the global importance of the October Revolution as a historical event, as well as the complexity of social relations in such circumstances, the objective of this paper is to look as thoroughly as possible into the correlations between the Revolution itself and social circumstances that preceded it. The paper interprets historical data and examines the main arguments within theories of revolutions. The focus is on structural factors and the analysis presented by Theda Skocpol, with an additional emphasis on the role of the proletariat. The basic thesis is that one of the key conditions is the existence of branched networking of the peasant communes and workers’ associations, with sufficiently strong connections within the classes. That is, discontent with the economic situation and the weakening of the central government would not in themselves lead to revolutionary events, just as joint activities of the proletariat and the leaders of opposition parties should not be neglected.
Keywords: revolution; causes; structural factors; class consciousness; discontent; Theda Skocpol